2021
DOI: 10.1007/s40262-021-01047-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposures of Phenylacetic Acid and Phenylacetylglutamine Across Different Subpopulations and Correlation with Adverse Events

Abstract: Background Elevated plasma ammonia is central to the pathogenesis of hepatic encephalopathy. Sodium phenylacetate or glycerol phenylbutyrate is approved for urea cycle disorders, but limited clinical data are available for hepatic encephalopathy. Phenylacetic acid (PAA) plasma exposure has been reported to correlate with neurologic adverse events in patients with cancer but not in patients with urea cycle disorders or hepatic encephalopathy. Ornithine phenylacetate, an intravenous dosage form of the l-ornithin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Population PK modeling identified that PAA exposure was approximately 36% higher in patients with C-P C than in patients with C-P B. This derivation agreed with the observed PAA concentration at steady state from study HE209, where C-P C patients had a 35% higher exposure to PAA versus C-P B patients [8].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Population PK modeling identified that PAA exposure was approximately 36% higher in patients with C-P C than in patients with C-P B. This derivation agreed with the observed PAA concentration at steady state from study HE209, where C-P C patients had a 35% higher exposure to PAA versus C-P B patients [8].…”
Section: Discussionsupporting
confidence: 78%
“…That renal dysfunction does not alter PAA exposure confirmed the hypothesis that the formation of PAGN is an irreversible process, thus the accumulation of PAGN in blood circulation due to reduced renal excretion would not alter the rate of PAGN formation. As such, renal dysfunction is not expected to change the removal of free ammonia in plasma circulation either, as observed from study HE209 [ 8 ]. To confirm this derivation, the present population PK model was applied to the PK data from a newly completed renal impairment study that included patients with severe renal impairment.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations